2020
DOI: 10.1111/ans.16203
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of 1241 patients to identify predictors of negative appendicectomy

Abstract: Background: Acute Appendicitis is the most common surgical presentation within Australia. Despite the increasing use of radiological investigations to aid clinical diagnosis, many appendectomies result in a histologically normal appendix. This study examines the histological negative appendicectomy rate (NAR) in a metropolitan hospital and determine factors associated with a negative appendicectomy (NA). Methods: Patients who underwent emergency appendicectomy for suspected acute appendicitis at Logan Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Our study is in keeping with the literature which shows female patients have higher negative appendectomy rates and morbidity associated with it [ 21 , 26 , 27 , 28 ]. Mackey et al recently identified factors that may be associated with higher negative appendicectomies, including independent factors such as age below 27, duration of symptoms for more than 48 h, normal leucocyte count, use of single imaging modality (ultrasound or CT) and time to operation greater than 24 h. Combination of factors like symptoms more than 48 h, normal leucocyte count, and a macroscopically normal intraoperative appendix may also be associated with a negative appendicectomy, but they also discussed that an intraoperatively normal looking appendix was histologically confirmed as normal only in 41%, hence the decision to not perform an appendicectomy in the absence of other pathologies still requires further studies where long-term effects of the practice are highlighted [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is in keeping with the literature which shows female patients have higher negative appendectomy rates and morbidity associated with it [ 21 , 26 , 27 , 28 ]. Mackey et al recently identified factors that may be associated with higher negative appendicectomies, including independent factors such as age below 27, duration of symptoms for more than 48 h, normal leucocyte count, use of single imaging modality (ultrasound or CT) and time to operation greater than 24 h. Combination of factors like symptoms more than 48 h, normal leucocyte count, and a macroscopically normal intraoperative appendix may also be associated with a negative appendicectomy, but they also discussed that an intraoperatively normal looking appendix was histologically confirmed as normal only in 41%, hence the decision to not perform an appendicectomy in the absence of other pathologies still requires further studies where long-term effects of the practice are highlighted [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mackay et al suggested that a delay in surgery beyond 48 h may be a predictor of negative appendicectomy, as the urgently operated patients usually have a clear presentation, whereas patients where diagnostic laparoscopy is the final investigation, an appendicectomy may be done contributing to morbidity associated with surgery. Instead, they suggest that the role of re-imaging needs consideration as a cost-effective and less invasive option [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though this is in contrast to some of the existing literature. 8, 19,24,25 , other studies have suggested WBC is not a predictor of AA. 26 Furthermore it has been suggested that WBC is a poor predictor of AA due to an unreliable speci city and sensitivity and there is no consensus for a reliable cut off value.…”
Section: Discussionmentioning
confidence: 93%